Assessing the efficacy and safety of autologous bone marrow injections in treating delayed union of long bone fractures: A retrospective analysis - Suresh Katakam; Boda Neeraja; Suguru Ravali; Srinivas Bachu (Asian Journal of Medical Sciences, 2023)
Background: Delayed union in long bone fractures poses a significant clinical challenge, necessitating effective treatment solutions. The urgency for novel and effective treatment modalities is ever-increasing, especially considering the prevalence and complications associated with delayed union. Aims and Objectives: This retrospective analysis aims to assess the safety and efficacy of autologous bone marrow injections in treating delayed union in a diverse cohort of individuals with long bone fractures. Materials and Methods: The study includes 100 individuals aged 21–69 with varying fracture types. Fracture classifications comprised 40% closed fractures (n=40) and 60% open fractures (n=60). Notably, the femur had a higher prevalence of open fractures (n=30) than closed fractures (n=20). Tibia fractures demonstrated a similar propensity, with 25 open and 15 closed cases. Humerus fractures manifested an even distribution between open and closed categories (n=5 each), indicating their relative resilience to open fractures. Results: Union was attained in 82 cases, with a mean union time of 7.4 weeks post-the-third bone marrow injection. The timeframe for the union varied widely, ranging from 4 to 17 weeks. In eight instances where bone marrow injections failed to achieve union, alternative treatment via bone grafting was necessary. No significant complications were reported; however, minor discomfort was experienced by 13% of the patients and was effectively managed with over-the-counter analgesics. Conclusion: This retrospective analysis demonstrates the high efficacy and safety of autologous bone marrow injections in treating delayed union in long bones, making them a promising alternative treatment strategy with minimal complications.